0860 Pulse Wave Amplitude Drops During Sleep: Reference Values And Clinical Associations In A General Population. (12th April 2019) - Hirotsu, Camila; Marques-Vidal, Pedro; Vollenweider, Peter; Betta, Monica; Bernardi, Giulio; Siclari, Francesca; Haba-Rubio, Jose; Heinzer, Raphael
Abstract: Introduction: This study aimed to establish reference values of PWA-drop frequency and characteristics as well as their clinical associations in a general population sample. Methods: HypnoLaus is a population-based cohort in which 2, 162 individuals underwent full polysomnography (PSG) at home, clinical assessment and blood collection for biochemical analysis. Hypertension (HT) was defined as systolic blood pressure ≥140mmHg, diastolic blood pressure ≥90mmHg, or anti-HT treatment. Diabetes was defined as fasting glucose levels >7.0 mmol/L or use of anti-diabetic treatment. The occurrence of myocardial infarction, acute coronary syndrome or stroke were assessed and adjudicated by a panel of expert. PWA-drops with amplitude >30% and duration >4 heartbeats derived from photoplethysmography, were identified as autonomic arousal (AA) by a validated algorithm. AA mean duration (s) and index (number per hour of sleep) were divided into quartiles and included in multivariable-adjusted logistic regression analysis. Results: 2, 143 participants (56.5±17.8 years, 51.0% women, 9.9% diabetes, 41.3% hypertension, 4.4% CVD) were included in the study. Median (interquartile range) of AA mean duration and AA index were 13.5 (12.0-15.4) s and 50.1 (36.1-63.5) events/h, respectively. After adjustment for sex, age, body mass index, apnea-hypopnea index, total sleep time and smoking, increasing AA mean duration (p-for-trend=0.006) and decreasing AA index (p-for-trend=0.037) were independently associated with prevalent HT and CVD, respectively. After adjustment for alcohol consumption and the same covariates, increasing AA mean duration was independently associated with prevalent diabetes (p-for-trend=0.012). Conclusion: PWA-drops are commonly observed during sleep and are independently associated with HT, CVD and diabetes in the general population. Support (If Any): Leenaards Foundation, FBM, and SNF.